Systematic Review of Sustainable Development Goals in Higher Education Institutions: First Five Years of Agenda 2030 - Solís Espallargas, Carmen; Ruiz-Morales, Jorge; Valderrama-Hernández, Rocío; Alcántara-Rubio, Lucía (Pedagogika, 2023)
This paper presents a systematic review of the scientific evidence regarding the Sustainable Development Goals (SDGs) in universities at the international level in the first 5-year period since the 2030 Agenda (2015–2020). The search comprises a selection of 63 articles published in Web of Science, Scopus, and Google Academic. This study analyses the main research trends, objectives, methodologies, and research tools. The paper concludes with the identification of barriers and limitations.